Detailed modeling of two diode photovoltaic module using MATLAB simulik - Habbati Bellia Assia; Moulay benine Fatima (Institute of Advanced Engineering and Science, 2019)
This paper proposes an accurate model of Photovoltaic Module. The model is presented in details and simulated by Matlab Simulink. The PV module is presented as a two diode model with the series’ and parallels’ resistances. The method is used to obtain the parameters of the module by using data provided by the manufacturer. To verify the accuracy of the proposed model, a comparison is done between the present results and those in a previous paper in which the single diode detailed model was studied. The same type of modules (PWX 500) is used to compare and validate results. The weather data as illumination and temperature are taken as input variables when current and Power are output variables. For the validation of the proposed model, it is used to power a resistive load by using a boost converter controlled by à Maximum Power Point Tracking method. The proposed method is very detailed and can be useful for PV researchers for their works.